Apatinib-treated advanced medullary thyroid carcinoma: a case report - Chen, Kan (Onco Targets Ther, 2018)
Medullary thyroid carcinoma (MTC) is a rare malignancy originating from calcitonin-producing parafollicular C cells of the thyroid. Neither radiotherapy nor chemotherapy has demonstrated durable objective responses in patients with advanced MTC. Vandetanib and cabozantinib are the 2 tyrosine kinase inhibitors recently approved by the US Food and Drug Administration, which are not affordable for most Chinese patients. Herein, we report a case of an MTC patient who responded to apatinib, a Chinese homemade tyrosine kinase inhibitor-targeted vascular endothelial growth factor receptor. The patient was treated with thyroid lobectomy but developed MTC with extensive metastasis. The levels of serum calcitonin and carcino-embryonic antigen were much higher than the normal range. Apatinib was given at a dose of 500 mg daily and adjusted according to tolerance. Sixteen weeks following apatinib administration, the patient achieved a partial response, which lasted more than 9 weeks. No severe toxicity or drug-related side effect was observed during the treatment. Therefore, apatinib could be a new option for the treatment of advanced MTC.